2021
DOI: 10.1007/s00122-021-03818-x
|View full text |Cite
|
Sign up to set email alerts
|

An adult plant stripe rust resistance gene maps on chromosome 7A of Australian wheat cultivar Axe

Abstract: Australian wheat cultivar Axe produced resistant to moderately resistant stripe rust responses under eld conditions and was exhibiting seedling response varying from 33C to 3+ under greenhouse conditions. Experiments covering tests at different growth stages (2 nd , 3 rd and 4 th leaf stages) demonstrated the clear expression of resistance at the 4 th leaf stage under controlled-environment greenhouse conditions. A recombinant inbred line (RIL) population was developed from the Axe/Nyabing-3 (Nyb) cross. Genet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…3ce and Supplementary Table 22). Some associated regions were co-located with known, but not yet cloned resistance genes loci such as Yr17 (2AS) 26,27 and Yr75 (7AL) 38 , which have been widely deployed in elite cultivars (Fig. 3c-e and Supplementary Table 23).…”
Section: Genome-wide Association Mapping For Yellow Rustmentioning
confidence: 99%
“…3ce and Supplementary Table 22). Some associated regions were co-located with known, but not yet cloned resistance genes loci such as Yr17 (2AS) 26,27 and Yr75 (7AL) 38 , which have been widely deployed in elite cultivars (Fig. 3c-e and Supplementary Table 23).…”
Section: Genome-wide Association Mapping For Yellow Rustmentioning
confidence: 99%
“…Our data shed light into the potential employment of the effective Lr genes like Lr2a, Lr28 and Lr19 that are of interest to wheat breeding programs to improve the resistance of Iranian wheat cultivars against leaf rust. terization of novel resistance sources is the prerequisite and most important strategy for controlling rust diseases in wheat and pyramiding these genes for durable resistance 33,34 . The rapid evolution of pathogens due to fungicide application, environmental conditions and also narrow genetic base of resistance genes in improved wheat genotypes can easily lead to the breakdown of the resistance genes 17,35 .…”
Section: Discussionmentioning
confidence: 99%
“…A locus conferring ASR was controlled by a major gene, Yrzhong12 -1, located in the interval of SSR markers Xcfd20 (3.1 cM) and Xbarc121 (4.9 cM) on chromosome 7AL (Ma et al, 2015 ). Kanwal et al ( 2021 ) identified the adult-plant stripe rust resistance gene Yr75 in the Australian wheat cultivar Axe and mapped the gene on the long arm of chromosome 7A, and the two SNP markers sunKASP_430 and sunKASP_427 were closely linked to the gene.…”
Section: Discussionmentioning
confidence: 99%